Modeling bidding competitiveness and position performance in multi-attribute construction auctions - Pablo Ballesteros-Pérez; Maria Luisa del Campo-Hitschfeld; Daniel Mora-Melià; David Domínguez (Operations Research Perspectives, 2015)
Currently, multi-attribute auctions are becoming widespread awarding mechanisms for contracts in construction, and in these auctions, criteria other than price are taken into account for ranking bidder proposals. Therefore, being the lowest-price bidder is no longer a guarantee of being awarded, thus increasing the importance of measuring any bidder's performance when not only the first position (lowest price) matters.
Keywords: 330; Bidding; Tender; Auction; Competitiveness; Performance; Kumaraswamy